Effect of ketamine and esketamine on RNA expression and its relevance for depression: A systematic review - Claudia Pisanu; Rosana Carvalho Silva; Mattia Meattini; Massimo Gennarelli; Bernhard T. Baune; Alessio Squassina; Alessandra Minelli (Pharmacological Research)
Treatment-resistant depression (TRD) remains a challenge in psychiatry, necessitating novel therapeutic strategies beyond traditional monoaminergic antidepressants. Ketamine and its S-enantiomer esketamine have demonstrated rapid and robust antidepressant effects in TRD, probably through mechanisms involving glutamatergic modulation, neuroplasticity, and anti-inflammatory properties. However, the molecular underpinnings of these effects are not yet understood. This systematic review aimed to synthesize evidence from human and in vitro studies evaluating transcriptional changes associated with ketamine and esketamine treatment, to identify potential biomarkers and clarify molecular pathways relevant to their antidepressant properties. A systematic search conducted on PubMed and Scopus identified 12 studies assessing RNA expression following ketamine or esketamine treatment in patients with unipolar or bipolar depression or in human-derived cell models. Eligibility and quality were evaluated using PRISMA guidelines and a modified version of Downs and Black checklist. Twelve studies met inclusion criteria, only one of which explored the effect of esketamine, while all others focused on racemic ketamine. Five studies examined peripheral blood gene expression in patients with TRD, while seven assessed mRNA changes in vitro using human-derived cells. Transcriptome and candidate gene expression studies revealed modulation of genes and pathways related to glutamatergic signaling (GRM2, GRIN2D), immune regulation (STAT3, CCL22, IL6), and neuroplasticity (IGF2). No consistent peripheral biomarkers emerged, but transcriptional profiling revealed dynamic molecular responses to ketamine and esketamine. Ketamine and esketamine induce diverse transcriptional changes implicating neuroplastic, inflammatory, and metabolic pathways. Transcriptomic profiling offers a promising approach for uncovering biomarkers and mechanisms of antidepressant response, warranting further multi-omics, large-scale studies.